The Implementation of Project-Based Learning (PjBL) in Biology Learning on Genetic Concepts - Herliyanti, Adinda; Putri, Dea Della; Usman, Usman; Sujiman, Sujiman (International Journal of Biology Education Towards Sustainable Development, 2024)
This study analyzed the implementation of Project Based Learning (PjBL) learning model in biology learning on genetic concepts of grade XII at one of the public high schools in Tangerang Regency. The purpose of the study was to evaluate the effectiveness of PjBL in improving students' learning outcomes and their engagement in the learning process. The research was conducted using descriptive method which included one learning cycle with four stages: planning, implementation, observation, and reflection. The results showed that the implementation of PjBL was able to improve students' active participation, creativity, as well as learning outcomes, with most students scoring above 90. However, some students with scores below 80 showed a lack of engagement in the group. The PjBL model proved effective in creating meaningful and in-depth learning experiences for students.